Rice Stock Monitoring: A Smart-home Based System - Hikmah Adwin Adam; Marliana Sari; Wiwin Sry Adinda Banjarnahor; Orli Binta Tumanggor; Daya Februwanti Gultom (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Monitoring systems have undergone numerous developments and improvements. Smart-home monitoring is one of the categories of monitoring systems which can be accessed remotely. Rice monitoring is one type of smart-home based monitoring that can be performed. In order to prevent households from experiencing a sudden lack of rice stock, it is essential to closely monitor the stock of rice. The Smart-home Based Rice Monitoring Design is an innovation created by earlier researchers for the benefit of the community, particularly households. This system is constructed with a microcontroller and a load cell sensor. To operate this device, user enters the weight of the rice using the keypad, and presses the fence button to release the rice from the container. In the meantime, pressing the star button on the keypad will delete or clear the entered numbers. The servo will then operate to open the valve, allowing the rice to fall, and close the valve when the weighing process is complete. A load cell sensor will perform the weighing process, and a 16x2 LCD will display the rice weight output process. All data processed through ESP32 will be transmitted to Firebase. The development of the application was planned using the MIT App Inventor website. To create applications on MIT App Invertor and Realtime Database on Firebase, an internet connection and an active email address are required.